Fostering Effective School Leadership for Disciplined Excellence - Agustyawati, Dwi; Farisatma (International Journal of Learning Reformation in Elementary Education, 2024)
This study aims to investigate the impact of the principal's leadership style on teacher discipline levels at SD Negeri 2 Wameo, Baubau, Indonesia. The study employs a quantitative research method, with a total of 37 respondents in the population and the same number of respondents in the sample. The data collection methods include questionnaires and documentation, and the analytical method used in this research is simple linear analysis. The findings of the research show that there is a significant influence between the principal's leadership style and teacher discipline levels. The calculated t-value (3.060) is greater than the t-table value (1.689) and has a significant probability value of 0.04 which is less than 0.05. Therefore, the principal's leadership style has an impact on teacher discipline levels at SD Negeri 2 Wameo. The R square value of 0.221 indicates that the principal's leadership style influences teacher discipline levels by 22.1%, while the remaining 77.9% is affected by other factors that the researchers did not test.